Analysis of the relationship between municipal management and vulnerability to the COVID-19 pandemic in brazilian municipalities (Research, Society and Development, 2021)
This study seeks to analyze the relationship between municipal management (represented by the adoption of management instruments) and vulnerability to the COVID-19 pandemic in Brazilian municipalities. As proxies for municipal management and vulnerability, the Municipal Management Index (IGM) and the Municipal Vulnerability Index to COVID-19 (IVMCOVID-19) were used, respectively. The indexes were composed of indicators extracted from the Municipal Basic Information Survey (MUNIC), published by the Brazilian Institute of Geography and Statistics and the Votorantim Institute. The relationship between IGM and IVMCOVID-19 was analyzed using regressions estimated by the Ordinary Least Squares Method and quantile regressions. The main results showed that municipal management reduces the municipality's vulnerability to COVID-19. The statistical evidence on the role of the municipality in leading the COVID-19 crisis motivated presents that municipal management, by favoring the development and adoption of public policies, also acts as a reducing agent of vulnerability to COVID-19. In this sense, the implementation of management tools must be incorporated as a commitment by the local authorities to create adaptive capacity to face this and other crises.